2019
DOI: 10.1101/655274
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paying Attention to Speech: The Role of Cognitive Capacity and Acquired Experience

Abstract: Managing attention in multi-speaker environments is a challenging feat that is critical for human performance. However, why some people are better than others in allocating attention appropriately, remains highly unknown. Here we investigated the contribution of two factors -Cognitive Capacity and Acquired Experience -to performance on two different types of Attention task: Selective Attention to one speaker and Distributed Attention among multiple concurrent speakers. We compared performance across three grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 56 publications
(67 reference statements)
1
5
0
Order By: Relevance
“…Moreover, pitch separation between two competing speakers (operationalized as same vs. different biological gender) also improved performance, but only when spatially separated. Critically, although Distributed attention is overall more difficult than Selective Attention, resulting in reduced performance in this study as well as previous work (Baldock et al, 2018; Best et al, 2006; Brungart, 2001; Koelewijn et al, 2014; Lambez et al, 2019), spatial separation affected performance on both tasks in a similar fashion, with no significant interaction between them. The lack of a difference between the effects of spatial cues on these two extremely different types of attentional tasks leads us to suggest that spatial cues play a limited role in directing top-down attention in multi-speaker environment, beyond their contribution to stream segregation.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, pitch separation between two competing speakers (operationalized as same vs. different biological gender) also improved performance, but only when spatially separated. Critically, although Distributed attention is overall more difficult than Selective Attention, resulting in reduced performance in this study as well as previous work (Baldock et al, 2018; Best et al, 2006; Brungart, 2001; Koelewijn et al, 2014; Lambez et al, 2019), spatial separation affected performance on both tasks in a similar fashion, with no significant interaction between them. The lack of a difference between the effects of spatial cues on these two extremely different types of attentional tasks leads us to suggest that spatial cues play a limited role in directing top-down attention in multi-speaker environment, beyond their contribution to stream segregation.…”
Section: Discussionsupporting
confidence: 77%
“…Rather, they invite a more flexible account of the processing bottlenecks within the speech processing system, which takes into consideration the perceptual and cognitive load imposed by competing stimuli in a given context, in line with load theory of attention 88,90,9799 . As observed here, this allows for some degree of parallel processing of concurrent speech, at least under conditions where these loads are not excessively high, but are similar to those encountered in real-life 93 .…”
Section: Discussionmentioning
confidence: 63%
“…Supporting this perspective, others have also observed that the level of processing applied to task-irrelevant stimuli can be affected by task demands 91,92 . Moreover, individual differences in attentional abilities, and particularly the ability to process concurrent speech, have been attributed partially to working memory capacity, a trait associated with the availability of more cognitive resources 39,9385 but cf. 96 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stimuli and paradigm used here were similar to that used in a previous behavioral study (Lambez et al 2020). Participants were presented with sequences of short mono-syllabic Hebrew nouns (e.g., "Kad"; pitcher in Hebrew).…”
Section: Stimuli -Attention Taskmentioning
confidence: 99%